Study on prevalence of cigarette smoking among a sample of students of technical institute of Babylon - Israa Dawood Salim, (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the prevalence of smoking among students, and to identify the reasons for smoking. Method: The cross-sectional, descriptive and analytical study was conducted from April 1 to May 9, 2019, at the Technical Institute, Al-Furat University, Babylon, Iraq, and comprised students of either gender who were selected randomly. Data was collected through structured interviews using a questionnaire. Data was analysed using SPSS 24. Results: Of the 147 subjects, 115(78.2%) were males and 32(21.8%) females. The largest age group was 19-28 years 125(85%), and 115(78.2%) hailed from rural areas. There were 78(53%) smokers; 73(63.5%) from among males and 5(15.6%) from among females. The most cited reason for smoking was feeling of enjoyment 40%. Smoking was significantly associated with age, gender as well as level and type of education (p<0.05). The association of friends and family with the smoking habit was significant (p<0.05). Among the smokers, 72(92.3%) were aware of the harmful effects of the habit (p<0.05). Conclusion: Cigarette smoking was found to be widespread among the students. Keywords: Smoking, Family, Tobacco, Habits, Masculinity, Students, Smokers.